Escola particular em Entre Ríos: analisando os motivos das famílias para escolher escolas secundárias para seus filhos - KUMMER, VIRGINIA (Universidad Nacional del Litoral, 2020)
This article analyzes the reasons why families choose to send their children to public secondary schools that are managed by privates. The studyfocused on the city of Paraná, capital of the province ofEntre Ríos, Argentina. This issue has gained relevancefor constituting a problem that has been always presentthroughout the history of Argentine educational system.Reality shows that, at least, an important number ofArgentine provinces are characterized by an exodusof middle-class sectors to the private offer, this beingin no way an exclusive feature noticed for secondaryschools but also for other levels of the education system.As regards the applied methodology, the analysis wasbased on a set of semi-structured interviews held with parents of children attending private schools. To thisend, four private schools in the city that were consideredrepresentative at a theoretical level and defined by theiruniqueness and idiosyncratic character were selected bymeans of an intentional sampling. Results indicated thatprivate schools offer differentiated education, which isregarded by families as an appropriate strategy to plantheir children’s future. Different reasons such as familytradition, discipline, social support, secularism, andthe institution size constitute the roots of this choice.